THE SHORT TERM CLIMATIC SENSITIVITY OF CARBONATE AND SILICATE WEATHERING FLUXES: INSIGHT FROM SEASONAL VARIATIONS IN RIVER CHEMISTRY - Tipper E.T.; Bickle M.J.; Galy A.; West A.J.; Pomi?s C.; Chapman H.J. (My University, 2006)
Large seasonal variations in the dissolved load of the headwater tributaries of the Marsyandi river (Nepal Himalaya) for major cations and 87Sr/86Sr ratios are interpreted to result from a greater dissolution of carbonate relative to silicate at high runoff. There is up to a 0.003 decrease in strontium isotope ratios and a factor of 3 reduction in the Si(OH)4/Ca ratio during the monsoon. These variations, in small rivers sampling uniform lithologies, result from a different response of carbonate and silicate mineral dissolution to climatic forcing. Similar trends are observed in compiled literature data, from both Indian and Nepalese Himalayan rivers. Carbonate weathering is more sensitive to monsoonal runoff because of its faster dissolution kinetics. Silicate weathering increases relative to carbonate during the dry season, and may be more predominant in groundwater with longer water-rock interaction times. Despite this kinetic effect, silicate weathering fluxes are dominated by the monsoon flux, when between 50% and 70% of total annual silicate weathering flux occurs. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CHEMICAL WEATHERING; CLIMATE CHANGE; CLIMATE FORCING; DISSOLVED LOAD; HEADWATER; ISOTOPIC RATIO; STRONTIUM ISOTOPE